(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2025)
This article provides an extended comparative literary analysis of James Joyce’s modernist masterpiece Ulysses (1922) and Chingiz Aytmatov’s lyrical novella Jamila (1958). Despite their distinct cultural origins—urban Irish modernity and rural Soviet Kyrgyzstan—both works transform ordinary human experiences into narratives of mythic resonance, exploring universal themes of identity, freedom, tradition, and moral choice. Joyce employs complex interior monologue, intertextual mythic structuring, and linguistic experimentation to elevate the mundane into the epic. Aytmatov, through lyrical realism and emotional narrative clarity, transforms a simple wartime love story into a timeless symbol of courage and authenticity. The research demonstrates that comparative literary analysis not only bridges cultural and stylistic divides but also enriches the interpretation of each text by highlighting shared humanistic concerns.